Diversidade oculta em espécies de Pyrrhulina Valenciennes, in Cuvier & Valenciennes (Characiformes, Lebiasinidae) com base no DNA barcoding - Souza, Taina Barbosa de (2021)
Characiformes is one of the most diverse and speciose order among neotropical fish, with about 2220 distributed species and 234 genera. Small species that are often neglected in conservation studies deserve to be highlighted. The Lebiasinidae family is composed of a considerable diversity of small to medium-sized species and is widely distributed in the hydrographic basins of South America. The genus Pyrrhulina is the second most speciose, but it presents several taxonomic problems among the Lebiasinids. Therefore, in order to seek to understand the genetic diversity of some Pyrrhulina species, therefore, assisting in the discovery of potential cryptic species, the present work aimed to carry out a study based on DNA Barcoding of Pyrrhulina specimens from different regions, both from the Paraguay basin and from adjacent basins. Therefore, a fragment of the Cytochrome c oxidase subunit I gene, used as DNA Barcode for vertebrate species, was used for detection and identification of MOTUs representing the genus in the study areas, through methods based on coalescence and genetic distance, aiming to detect the presence of cryptic species. The results revealed that, among the sampled specimens, there are 9 distinct MOTUS, here referred to as Pyrrhulina aff. australis (MOTU 1 and 5), P. australis (MOTU 2, 3 and 4), Pyrrhulina sp. (MOTU 6), P. cf. brevis (MOTU 7), P. spilota (MOTU 8) and P. filamentosa (MOTU 9). Genetic distances were compared between the detected units. The highest average of the interspecific distance was verified between P. filamentosa and P. cf. brevis (15.58%), and the lowest mean was among P. aff. australis and P. australis (2.52%). Regarding the MOTUs, the highest interspecific mean was also between the MOTUs of P. filamentosa and P. cf. brevis (MOTU 7 and 9), and the shortest inter-MOTU distance were observed between P. australis (MOTU 3) and P. aff. australis (MOTU 5). These results show a high diversity within Pyrrhulina, aiding in the molecular characterization of the species, being a big step in studies of delimitation of species of the genus.